Perancangan Mesin Pencetak Briket Limbah Pelepah Sawit Sistem Hidrolik di Kota Bontang - Ratnawati, Ratnawati; Yuono, Lukito Dwi; Rozy, Fahru; Aswar, Aswar (TURBO [Tulisan Riset Berbasis Online], 2025)
Oil palm frond waste is an abundant biomass that has not been optimally utilized in Bontang City, East Kalimantan, with the potential for processing into briquettes as an alternative energy source. This study aims to design and produce a briquette molding machine for oil palm frond waste with a hydraulic system using SolidWorks 2011 software, and to determine the effect of pressure variations on the quality of the resulting briquettes. The research method includes literature study, 3D design, machine construction, and testing of components and briquette results. The machine is designed with a UNP 80 frame, a cylindrical mold, a press piston, a hydraulic jack, and a return spring. Tests were carried out at three pressure variations, namely 50 bar, 100 bar, and 150 bar. The results showed that the pressure of 150 bar was 0.00182 g/cmÂ³, while the lowest water content was also found at a pressure of 150 bar, namely 8.33%, resulting in denser and more flammable briquettes. The lowest ash content was 5.71% at 100 bar, indicating the least combustion residue at medium pressure. Overall, the hydraulic briquette press was able to operate stably and produce briquettes with quality that meets biomass fuel standards. This research is expected to provide an alternative solution for utilizing biomass waste while increasing the productivity of (UMKM) in Bontang City.